On Transient Response of Piezoelectric Transducers - Fa, Lin; Mou, Jinpeng; Fa, Yuxiao; Zhou, Xin; Zhang, Yandong; Liang, Meng; Ding, Pengfei; Tang, Shaojie; Yang, Hong; Zhang, Qi; Wang, Maomao; Li, Guihui; et al. (Frontiers in Physics, 2018)
We report a new model in analysis of the spherical thin-shell piezoelectric transducers based on the principle of linear superposition. We have established a parallel-connected circuit-network to describe a spherical thin-shell piezoelectric transducer. When excited by a signal with multiple frequency components, this network would be a series of parallel-connected equivalent-circuits. Each circuit would have a distinctive radiation-impedance arising from an individual frequency component. Each frequency component would act independently on the electric/mechanic-terminals. A cumulative output-signal from the mechanic/electric-terminals is measured as the acoustic/electric output. As a prototype example in testing the new model, we have designed two spherical shin-shell transducers, applied a gated sine electric-signal as the initial excitation, and recorded the experimental information. The transient response and the output signals are calculated based on the new model. The results of calculation are in good agreement with that of experimental observation.